2015
DOI: 10.1080/1461670x.2015.1046995
|View full text |Cite
|
Sign up to set email alerts
|

The Powers that Tweet

Abstract: Citation: HLADIK, R. and STETKA, V., 2015. The powers that tweet: social media as news sources in the Czech Republic. Journalism Studies, 18(2), pp. 154-174. The study relies on a content analysis of a six-month sample of news articles collected in 2013 and focuses on social networking sites (SNSs), namely Facebook and Twitter, in their capacity as acknowledged sources in the agenda of traditional news media in the Czech Republic. The results include information on the differences between tabloid and quality p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 36 publications
1
12
0
1
Order By: Relevance
“…explicit violence). This may, in practice, limit opportunities for such content to make it into traditional media ( Broersma and Graham, 2012 ; Hermida and Thurman, 2008 ; Hladík and Štětka, 2015 ; Knight, 2012 ; Mare, 2013 ; Paulussen and Harder, 2014 ; Van Leuven et al, 2015 ; Vis, 2013 ). As citizen journalists, alternative media and journalists, and newsrooms learn about each other’s expectations, their practices may eventually converge ( Hänska and Shapour, 2013 ).…”
Section: Engagement and Media Representationsmentioning
confidence: 99%
“…explicit violence). This may, in practice, limit opportunities for such content to make it into traditional media ( Broersma and Graham, 2012 ; Hermida and Thurman, 2008 ; Hladík and Štětka, 2015 ; Knight, 2012 ; Mare, 2013 ; Paulussen and Harder, 2014 ; Van Leuven et al, 2015 ; Vis, 2013 ). As citizen journalists, alternative media and journalists, and newsrooms learn about each other’s expectations, their practices may eventually converge ( Hänska and Shapour, 2013 ).…”
Section: Engagement and Media Representationsmentioning
confidence: 99%
“…In the visual condition, the same attribution to Twitter was included and, moreover, supplemented by a screenshot of the tweet referred to in the news article. We decided to focus on this particular type of visualization since a recent previous study showed that journalists often use social media, from which they frequently take UGC, for textual rather than visual information (Hladìk and Ŝtêtka 2017).…”
Section: Visualizationmentioning
confidence: 99%
“…Nemusí se přitom prosit novinářů a vyjednávat si u nich prostor pro publicitu. 32 Proto je vhodné si poloţit otázky jako: Jakou roli hrají online sociální sítě v komunikaci veřejných institucí? Uvědomují si tyto instituce posun v komunikačním paradigmatu?…”
Section: Role Nových Médií a Jejich Vliv Na Komunikaciunclassified